Optimization of Zakat Fund Management in Improving the Welfare of Foster Children at Al-Ichlas Orphanage Surabaya: Sharia Economic Perspective - Ghanyfebriyan Moch Muqsit (Lavish Opulent Education, 2025)
Zakat is one of the instruments in the Islamic economic system that has strategic potential in poverty alleviation and improving welfare. This study aims to evaluate the extent to which the management of zakat funds implemented at the Al-Ichlas Orphanage in Surabaya can be optimized to improve the welfare of foster children from a sharia economic perspective. This study uses a descriptive qualitative method with a case study approach. Data collection techniques are carried out through direct observation, in-depth interviews, and documentation. The results of the study indicate that zakat management has been carried out in accordance with the basic principles of sharia, but has not been fully optimal. Limited human resources, lack of sharia-based financial management training, and the absence of accountability and transparency standards are the main obstacles. This study recommends strengthening the zakat reporting system, increasing sharia financial literacy, and strategic partnerships with official zakat institutions (LAZ) to achieve efficient and equitable zakat management. This study concludes that optimal, planned, and accountable management of zakat funds can provide a real contribution to improving the welfare of foster children. Therefore, it is necessary to strengthen the monitoring and evaluation system of the program and develop the capacity of human resources so that the benefits of zakat can be felt more widely and sustainably.